Efek gaya tekan pembuatan hibrid komposit berpenguat SiCw/Al2O3 dengan wetting agent Mg terhadap sifat fisik dan mekanik - Suarsana, K.; Suardana, N.P.G.; Negara, D.N.K.P.; Sunu, P.W.; Triadi, A.A.A. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2021)
The growing demand for metal-based materials in the manufacturing industry has prompted the development of composite materials that have better mechanical and physical properties than single materials. The development be done in order to obtain new materials that have better properties. The research was conducted using a powder metallurgy process, by varying the compressive force and holding time in order to determine the effect of the combination of compression and holding time on the mechanical and physical properties of composites. The variations in the compressive force are 20, 25, and 30 kN, with a holding time of 15, 30 and 45 minutes for each force. Research includes tests of density, porosity, hardness, wear and Scanning Electronic Microscope. The results of the density test showed that the highest density value was 2.982 gr/cm3 and the lowest porosity value was 13.074% at a compressive force of 25 kN, holding time of 45 minutes. The results of the highest hardness value 53.455  kg/mm2 at 30 kN, 45 minutes and the lowest wear value 2.15455E-05 gr at a pressure of 20 kN, 15 minutes. Based on the test results, the characteristics of the density are inversely proportional to the porosity, while the hardness and wear are influenced by the length of holding time in the moldof a composite using aluminum as a matrix needs too.